Respuesta :

Tasyha

Answer:

[tex] p_{1} = 0 \: . \: \: p_{2} = \frac{1}{2} [/tex]

Step-by-step explanation:

[tex]6 {p}^{3} \times {p}^{2} = {3p}^{4} \\ {6p}^{3 + 2} = {6p}^{5} = {6p}^{5} = {3p}^{4} \\ {6p}^{5} \div 3 = 3 {p}^{4} \div 3 \\ 2 {p}^{5} - {p}^{4} = {p}^{4} - {p}^{4} \\ {2p}^{5} - {p}^{4} = 0 \\ {p}^{4} (2p - 1) = 0 \\ {p}^{4} = 0 \\ 2p - 1 = 0 \\ [/tex]

[tex] \boxed{\bold{Answer:{\boxed{\green{\bold{p_{1} = 0 \: . \: \: p_{2} = \frac{1}{2}}}}}}} [/tex]

┈➤ . . ⇢ ˗ˏˋ⌦ ..♡ˎˊ˗ ꒰✈꒱   

╭─────────

┊╭─────────

┊✿꒷꒦ ☆○●□■

╰─────────

★ . ꜝꜞ ᳝ ࣪ hope that helped!  ʬʬ